INFLUENCE COMPETENCE, WORK DISCIPLINE, AND INTERNAL COMMUNICATION ON THE PERFORMANCE OF THE EMPLOYEES OF THE KUNINGAN REGENCY REGIONAL SECRETARIAT - Donis Kadarisman; Ila Nurul Haidah (International Journal of Management, Economic, Business and Accounting, 2022)
This study aims to determine: How much influence Competence, Work Discipline and Internal Communication have on the performance of the employees of the Kuningan Regency Regional Secretariat either partially or simultaneously. Location of Research Regional Secretariat of Kuningan Regency. The population of the employees of the Kuningan Regency Regional Secretariat, Kuningan Regency, amounted to 164 people, the sample used the Slovin formula, the number of samples was 62 people. The research design uses a quantitative approach, survey method, with data analysis techniques using Multiple Linear Regression analysis. The results of this study indicate: 1) There is a positive and significant influence partially Competence on the Performance of the Regional Secretariat of Kuningan Regency Employees. The magnitude of the positive influence of competence on performance is 43.3%; 2) There is a positive and significant influence of work discipline partially on the performance of the employees of the Kuningan Regency Regional Secretariat. The magnitude of the influence of Work Discipline on Performance is 50.3%; 3) There is a positive and significant influence of Internal Communication partially on the Performance of the Regional Secretariat of Kuningan Regency Employees. The magnitude of the influence of Internal Communication on Performance is 54.9%; 4) There is a positive and significant effect of Competence, Work Discipline and Internal Communication simultaneously on the Performance of the Kuningan Regency Regional Secretariat Employees. The magnitude of the influence of Competence, Work Discipline, Internal Communication on Performance is 22.6%.